The Evolution of the Georgian Notariat: From the StateControlled Soviet System to Professional Independence and Digital Modernization - Gogoladze, Marika; Shamatava, Irakli (European Scientific Journal, ESJ, 2026)
Following the dissolution of the Soviet Union and the restoration of Georgia’s state independence, a comprehensive transformation of legal systems began across the post-Soviet space, aimed at modernizing Soviet legal institutions and aligning them with European legal standards. In this process, an institutional reform of the notariat was carried out, resulting in the gradual evolution of the notarial system into a professionally independent legal institution. In a historical context, the notariat functioned as a strictly centralized state institution within the Soviet legal system, where notaries were public officials and their activities were subject to administrative control. This model was ill-suited to the demands of a market economy and private law, thereby necessitating institutional reform of the notariat in the post-Soviet period (Palmer, 2012; Smits, 2020). In the course of this process, a Latin-type (“independent”) notariat emerged and developed alongside the state notariat in some of the post-Soviet countries (Sukhitashvili, 2012, p. 25). This model is based on the professional independence of notaries and the safeguarding of private-law security (Zoidze, 2005). The present article aims to analyze the institutional transformation of the Georgian notariat in the post-Soviet period and assess the impact of legislative reforms on the development of the notarial profession. The study is based on a doctrinal and comparative legal analysis encompassing the comparison of Georgian legislation and European notary systems. It is noteworthy that Georgia was among the first countries to introduce online notarial services. Besides, the study examines the extent to which the transition from the Soviet state notarial model to a Latin-type notarial system has ensured the strengthening of the professional independence of notaries and the improvement of legal certainty in civil transactions in Georgia. According to the research hypothesis, the legislative and institutional reforms implemented in Georgia, have played a significant role in strengthening the notarial profession and enhancing the reliability of legal acts. Nevertheless, the further development of institutional mechanisms and practical legal instruments continues to pose a significant challenge to achieving the full effectiveness of the notarial system and its complete adaptation to the contemporary legal environment, particularly in the context of ongoing digital and technological transformation. The study argues that the Georgian experience reflects a broader pattern in which the hybridization of Latin legal principles with digital governance may constitute an emerging model of post-socialist legal modernization.